Magic Bee an ABC implementation for solving magic square puzzles - Elmido, Pamela Chloe R.; Uy, Tiffany Elaine Y. (Pamela Chloe R. Elmido, 2009)
Magic Squares are one of the interesting fields in recreational mathematics because of their mathematical properties. These puzzles give exciting challenge as they require every row, column and diagonal to add up to the same number which is known as the magic sum. A new approach is proposed which applies an Artificial Bee Colony Algorithm for constructing Magic Squares of order three up to order twelve. This ABC algorithm is a new nature-inspired population-based algorithm inspired by the foraging behavior of honey bee swarm. Results of the experiments show that a bee-inspired algorithm, specifically the ABC algorithm, is an efficient approach for generating Magic Squares.